Observation of tumour-induced reorganization in structural and functional architecture of the brain in three pre-surgical patients with left frontal-temporal brain tumour: a combination of MEG, DTI and neuropsychological assessment - Hanani Abdul Manan; Zamzuri Idris; Mohammed Faruque Reza; Wan Nor Azlen Wan Mohamad; Jafri Malin Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2017)
Visual function is mainly located within the bilateral hemisphere of the occipital lobes of the brain. However, our functional magnetoencephalography (MEG) result has demonstrated the reorganization of brain activity in the occipital area in patients with left-sided brain tumour. The results showed that brain laterality changes from bilateral to unilateral activation of the occipital area. Right occipital area (contralateral areas to the tumour), shows increase intensity of activation. Diffusion tensor imaging (DTI) with fibre tracking was performed to further investigate this brain laterality modification and the findings confirmed there is an alteration in the left hemisphere fibre optic tracts. This functional modification and changes of the brain laterality and optic tracts in the brain is suspected to be the result of tumour growth induced changes. The present observation will be discussed in term of the mechanism of tumour induced reorganization and changes with the corroborating evidence from MEG, DTI and neuropsychological assessment.